Impactos socioambientais da indústria de calcário no município de Simão Dias/SE - Carvalho, Josefa Rose Emanoelle Menezes (2017)
The mining industry is essential to human activities, given the use of its products in construction, sanitation, steel industries, motorists, among others. However, the continuous exploitation of resources that do not renew brings as a consequence changes in the landscape, soil and air and water conditions, and can also modify the quality of life of the people living in the vicinity of their area of influence. The municipality of Simão Dias / SE has a limestone industry that has been instigated there since the sixties of the last century, having since changed the environment and the way of life of the communities. For this reason, the objective of this research was to analyze the reflexes of the implantation of said industry in the municipality in order to identify the main positive and negative impacts related to it. For that, the quantitative approach was used, through the analysis of the subjects' discourse. To collect data, the semi-structured interview was used, applied to former employees, managers of public power and older residents of the settlements located around the project. The results pointed out the need to plan actions aimed at local development, in an articulated way between the public and private spheres and with the participation of the citizens, so that it is possible to think of a model of local development that encompasses the three dimensions of sustainability , ecological, economic and social.